Interaction of an elastic wave with a circular crack in a fluid-saturated porous medium - Galvin, Robert; Gurevich, Boris (American Institute of Physics, 2006)
We consider interaction of a normally incident time-harmonic longitudinal plane wave with a circular crack imbedded in a porous medium governed by Biot's equations of dynamic poroelasticity. The problem is formulated in cylindrical coordinates as a system of dual integral equations for the Hankel transform of the wave field, which is then reduced to a single Fredholm integral equation of the second kind. The solution of this equation yields elastic wave dispersion and attenuation in a medium containing a random istribution of aligned cracks. These dissipation effects are caused by wave induced fluid flow between pores and cracks. 2006 American Institute of Physics.